Penerapan Charger Controller type PWM pada Pembangkit Listrik Tenaga Pikohidro - Wijaya Kusuma; Anang Dasa Novfowan; Harrij Mukti K. (Elposys: Jurnal Sistem Kelistrikan, 2022)
This study aims to design a PWMtype charger controller, to discover the performance of the PWM type controller, to determine the compatibility of the PWM type charger controller and MPPT, and to analyze the performance of the PWM type charger controller in the PLTPH in JLC. The method of analysis of this study uses field data and is tested on the PWM type charger controller and the MPPT type charger controller. From the data, the two charger controllers are compared. The results showed that the PWM and MPPT charger controller performed well to cut off the load current when the battery was full, the PWM and MPPT charger controller performed well to disconnect the load when the battery began to run out. The PWM and MPPT charger controllers have the same charging speed, and the MPPT charger controller has good efficiency in the PLTPH system.